2000
DOI: 10.1093/carcin/21.5.893
|View full text |Cite
|
Sign up to set email alerts
|

Cell activation via CD44 occurs in advanced stages of squamous cell carcinogenesis

Abstract: Squamous cell carcinoma (SCC) derives from dysplastic or metaplastic stratified epithelia. The process of squamous cell carcinogenesis has been investigated for the potential role of the adhesion molecule CD44, whose standard form (CD44s) and isoforms generated by alternative splicing of variant exons are known to display altered expression during tumorigenesis in other systems. We have utilized an in vitro correlate of squamous cell carcinogenesis, in which progression stages from normal squamous epithelium t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Additionally, the functional role of CD44 has revealed different features of the molecule in the two histological subtypes. In SCC, only cells of the neoplastic stage can transduce subcellular signals via CD44 [26], whereas CD44s down-regulation in the NSCLC cell line H322, derived from a primary bronchioalveolar carcinoma of the lung, may confer a protective advantage by allowing escape from tumoricidal effector cells, including activated macrophages of the host, thus promoting tumorigenesis [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the functional role of CD44 has revealed different features of the molecule in the two histological subtypes. In SCC, only cells of the neoplastic stage can transduce subcellular signals via CD44 [26], whereas CD44s down-regulation in the NSCLC cell line H322, derived from a primary bronchioalveolar carcinoma of the lung, may confer a protective advantage by allowing escape from tumoricidal effector cells, including activated macrophages of the host, thus promoting tumorigenesis [27]. …”
Section: Discussionmentioning
confidence: 99%
“…A number of laboratories, including our own, have demonstrated that the binding of HA to CD44-expressing cells promotes intracellular Ca 2ϩ mobilization, which is a pre-requisite for the onset of a variety of biological activities [Bourguignon et al, 1993Galluzo et al, 1995;Bruno et al, 2000;Partida-Sanchez et al, 2000]. Although the cellular and molecular mechanisms involved in HA/CD44-mediated Ca 2ϩ signaling are currently not well understood, one of the likely pathways involves the phosphatidylinositol cascade that leads to Ca 2ϩ release from intracellular stores [Berridge, 1993;Yoshida and Imai, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…This is well known for p53 protein, where over expression usually indicates mutation. The same phenomenon is being increasingly recognized for other markers; for example, CD44 protein is expressed on the cell surface of squamous carcinoma cells in vitro , but the presence of the protein is independent of its function in signal transduction, which is essential for tumourigenesis11.…”
Section: Immunocytochemical Studies Of Malignancymentioning
confidence: 83%